Propuesta de Plan de Marketing Turístico de la Ruta de los Museos de la Ciudad de Loja - Álvarez Vega, Blanca Gabriela (2018)
The project called "PROPOSAL OF TOURIST MARKETING PLAN OF THE ROUTE OF THE MUSEUMS OF THE CITY OF LOJA", is an initiative developed with the purpose of contributing to the effective progress and to reactivate the tourist activity in the route of the museums of the city of Store. The general objective of the present study was: To elaborate a Tourist Marketing Plan for the route of the museums of the city of Loja; For this purpose, three specific objectives were set out: 1. To make a diagnosis about the current situation of the museum route in the city of Loja; 2. Propose a Tourist Marketing Plan for the route of the museums of the city of Loja and 3. Socialize the Tourism Marketing Plan of the route of the museums of the city of Loja. For the consequent development of the objectives, it was necessary to use appropriate methodologies and techniques, so the first objective was to use the bibliographic, analytical, inductive and descriptive method, which made it possible to diagnose the current situation of museums; Complementing the field study were used techniques such as direct observation, the survey and the interview that allowed to verify the current reality. Finally, it was considered necessary to perform an analysis of the internal and external factors for which the SWOT matrix was applied. In order to comply with the second objective, the analytical-synthetic method was used, which allowed analyzing and synthesizing the information obtained in the first objective and starting from this to develop the Tourist Marketing Plan of the route of the museums of the city of Loja. Finally, in order to fulfill the third objective, the technique of exposure was applied, which was supported by a power point presentation, which allowed us to present the work done and the results obtained during the development of this project. The results obtained are demonstrated by establishing the diagnosis of the current situation of the route of the museums of the city of Loja as well as with the proposal of the Marketing Plan in which it is presented, a tourist brand that will give identity to the route ; An advertising and promotion plan, a training plan and finally an itinerary with their respective script, which provide strong information on the route of the museums of the city of Loja and that will attract even more tourists visiting the city . Culminating with the present thesis, it was considered among the conclusions that one of the main weaknesses of the museum route is the disorganization and lack of budget destined for the operation of the route, which has totally limited its functionality. However, it should be emphasized that through the SWOT analysis it was possible to establish strong points that the route contains as the presence of competent entities with tourism and culture such as the National Institute of Cultural Heritage, Illustrious Municipality of Loja and the Ministry of Tourism entities that Can contribute and guarantee the revival of cultural tourism in the city and Loja. The recommendations made at the end of the present study are mainly aimed at museum administrators to be the main mentors to reactivate the tourist activity and in this way carry out the relevant management that helps to improve the functionality of the ROUTE DE THE MUSEUMS. It is also recommended that the competent entities organize and work jointly for the development of the tourist route of museums and the city in general